Analysis of radar precipitation estimation in Central Croatia (Rudarsko-geološko-naftni zbornik, 2017)
Good monitoring of precipitation is of great importance in many fields of human activity that use meteorological infor- mation. Precipitation is highly variable in space and time and therefore it is advisable to use tools that provide good spatial and temporal resolution of the phenomenon. The meteorological radar from the Radar Center of Bilogora is used for this purpose. However, radar precipitation is not measured directly but is estimated in a way that reflected electro- magnetic signal turns into precipitation using the Z-R relation. This paper analyses the period from 1. 12. 2015. to 31. 8. 2016., comparing the ground measurements of hourly accumulated precipitation from the main meteorological stations and radar associated pixels precipitation estimation. It was found that radar overestimates precipitation. It is possible to reduce such systematic radar estimation errors with a climatological bias adjustment.